2020
DOI: 10.1093/ageing/afaa038
|View full text |Cite
|
Sign up to set email alerts
|

Statin-induced autoimmune necrotizing myopathy with pharyngeal muscles involvement

Abstract: Statins are widely prescribed in the treatment of hypercholesterolemia. While their efficacy in the secondary prevention of vascular events is proven, their safety profile in older patients with multiple co-morbidities and polypharmacy remains questionable. Although rare, antihydroxy-3-methylglutaryl-coenzyme A reductase (anti-HMGCR) myopathy is a severe adverse effect of statins, manifesting as myalgias, proximal muscle weakness, muscle cell necrosis and rhabdomyolysis. We report an uncommon case of an autops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…Proximal upper limb-only weakness can be confused with shoulder girdle myopathy. Manifestation with dysphagia has also been reported [ 16 ]. If untreated, the symptoms become more severe with resultant muscle loss and weakness.…”
Section: Discussionmentioning
confidence: 99%
“…Proximal upper limb-only weakness can be confused with shoulder girdle myopathy. Manifestation with dysphagia has also been reported [ 16 ]. If untreated, the symptoms become more severe with resultant muscle loss and weakness.…”
Section: Discussionmentioning
confidence: 99%
“…Часто (до 25% случаев) отмечается дисфагия, которая повышает риск развития аспирационной пневмонии. Слабость дыхательной мускулатуры и в редких случаях мышц гортани может привести к нарушению функции дыхания и даже потребовать искусственной вентиляции легких [13]. Лицевая мускулатура затрагивается редко.…”
Section: клиническая картинаunclassified
“…Statin-associated necrotizing myopathy (SANM), characterized by symmetrical weakness and muscle enzyme elevations as a consequence of necrosis and regeneration of myofibers, is a rare disease that occurs in patients treated with statins [1][2][3]. Previous studies suggested that statins enhance the expression of 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMGCR), the enzymatic target of statins, in genetically susceptible patients, leading to the development of disease-specific antibodies against HMGCR [4][5][6][7][8][9]. SANM causes life-threatening hypoventilationmediated hypoxemia and hypercapnia, but therapeutic strategies for SANM have not been established yet.…”
Section: Introductionmentioning
confidence: 99%